(untitled) (Orfeu, 2020)
The growing output of scholar works, including in Brazil, inspired by Gjerdingen’s schematae theory, in parallel with the discussion on the musical topic theory,afterRatner’s issues,has stimulated the search for meanings resulting from the interaction between syntactic and semantic aspects in musical works, especially those ones developed between the 18th and 19th centuries. Such compositions, gathered from an amalgam of musicology with several other study areas, in music or related sujects, rekindle the debate about Rhetoric and Poetics as guidance for the compositional projects of authors from those times. In this way, the present article discusses André da Silva Gomes’s (1752-1844) creative strategies of focusing his thoretical manuscript Arte explicada do Contraponto.